Association between Interleukin-21, 23 and 27 Expression and Protein Level with Cytomegalovirus Infection in Liver Transplant Recipients - Afshari, A. (Int J Organ Transplant Med, 2020)
BACKGROUND: Cytokines have regulatory crosstalk with CMV infection leading to manage of post-liver transplantation virus-related outcomes. OBJECTIVE: To investigate the link between IL-21, IL-23 and IL-27 mRNA and protein level with active CMV infection, which was evaluated in reactivated and non-reactivated liver transplant recipients. METHODS: Two groups of liver transplant recipients were enrolled in this study—54 without and 15 with active CMV infection. 3 EDTA-treated blood samples were taken on day 1, 4, and 7 post-liver transplantation. Plasma and buffy coats of all samples were separated. All samples were analyzed for CMV reactivation using antigenemia technique. The separated plasma of positive samples was used for viral DNA extraction and protein evaluation. For evaluating the mRNA expression level by real-time PCR, RNA extraction and cDNA synthesis were done for all samples. Also, the protein level of studied genes was estimated by ELISA. RESULTS: The expression level of IL-21, IL-23A and IL-27A cytokine genes was increased in CMV reactivated liver transplant recipients in comparison with CMV non-reactivated ones; IL-27A expression pattern was significant (p=0.001) at all sampling times. IL-21 significantly increased on the 2(nd) and 3(rd) (p=0.028 and 0.01, respectively) sampling days in CMV reactivated compared with non-reactivated patients. The expression level of IL-23A cytokine significantly increased on the 3(rd) (p=0.017) sampling day in CMV reactivated compared with non-reactivated liver transplant recipients. CONCLUSION: Elevation in the expression level of IL-21, IL-23A and IL-27A mRNA and protein level in CMV reactivated patients emphasized on the antiviral role of these cytokines in CMV reactivated liver transplant recipients.